Phase diagram and low temperature scenario for a triangular triple dot system. (January 2016) - Xiong, Yong-Chen; Wang, Wei-Zhong; Yang, Jun-Tao; Luo, Shi-Jun
Abstract: We present a triangular triple quantum dot (TTQD) system with two dots connected parallelly to one conduction lead, and investigate the phase diagram, the electric transport, and the temperature-dependent magnetic moment at half filling. When the hopping between two connected dots t 12 = 0, and those between the connected dots and the side dot are symmetric t 13 = t 23, two connected dots form a spin triplet due to the Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction mediated by the dot-lead coupling and/or the hopping t 13 ( t 23 ). For t 13 = 0, the triplet is partially screened by the conduction leads at low temperature. Both the connected dots and the side dot contribute to the magnetic moment of the system. For any definite t 13, the triplet is totally screened by the conduction leads and the side dot, and the two-stage Kondo effect occurs. When t 12 increases beyond a critical t 12 c, two connected dots form a spin singlet and decouple from the side dot. In this case, the Kondo peak is strongly suppressed, indicating zero conductance, and only the localized side dot contribute to the magnetic moment at low temperature. When t 13 ≠ t 23, we find a crossover as t 12 increases, contrast to the first order transition of the symmetric case. Numerical renormalization group technique and physical arguments are used to obtain a detailed understanding of these problems. Highlights: A new TTQD model is presented. The ground state phase diagram in a wide range of the interdot hopping is clarified. The low temperature screening scenario and electric transport are investigated.